Comparison of Fasting Blood Sugar Levels and Ureum Levels In Diabetes Mellitus Patients and Diabetic Nephropathy Patients: Perbandingan Kadar Gula Darah Puasa Dan Kadar Ureum Pada Pasien Diabetes Melitus Dan Pasien Nefropati Diabetik - Adilla Cahya Ramadhani; Syahrul Ardiansyah (Academia Open, 2024)
General Background: Diabetes Mellitus (DM) is a chronic disease characterized by hyperglycemia. Specific Background: A severe complication of DM is diabetic nephropathy, marked by progressive kidney function decline. Blood sugar and urea levels serve as crucial indicators in diagnosing DM and its complications. Knowledge Gap: Limited comparative studies exist on fasting blood sugar and urea levels between diabetes mellitus patients and diabetic nephropathy patients. Aims: This study aims to compare fasting blood sugar levels and urea levels in diabetes mellitus patients and diabetic nephropathy patients. Results: Conducted from April to June 2024, this quantitative, laboratory experimental study sampled 30 diabetes mellitus patients and 30 diabetic nephropathy patients from RSUD dr. Wahidin Sudiro Husodo, Mojokerto City. Using the SPSS Mann-Whitney test, the study found significant differences (p=0.000) in fasting blood sugar levels (125.20±20.348 mg/dL vs. 221.07±65.545 mg/dL) and urea levels (13.30±2.059 mg/dL vs. 54.10±26.699 mg/dL) between the two patient groups. Novelty: This study provides novel insights into the metabolic differences between diabetes mellitus and diabetic nephropathy patients, emphasizing the progressive impact of high blood sugar on kidney function. Implications: The findings underscore the importance of early intervention and continuous monitoring of blood sugar and urea levels to prevent or mitigate diabetic nephropathy in DM patients. Highlights : Significant Differences: The study found significant differences in fasting blood sugar and urea levels between diabetes mellitus and diabetic nephropathy patients. Metabolic Insights: Provides insights into the metabolic impact of high blood sugar on kidney function in diabetic nephropathy patients. Clinical Implications: Highlights the need for early intervention and continuous monitoring to prevent or mitigate diabetic nephropathy in DM patients. Keywords : Diabetes Mellitus, Diabetic Nephropathy, Fasting Blood Sugar Levels, Urea Levels, Kidney Function